PROFIL PENGOBATAN PASIEN DIABETES MELITUS RAWAT JALAN DI DEPO FARMASI UMUM RSUD ULIN BANJARMASIN PERIODE JANUARI – MARET 2019 - Aulia Rahim; Rusiyana Rusiyana; Luluk Purwantini (Jurnal Farmasi IKIFA, 2021)
Diabetes mellitus (DM) is a chronic and progressive disease that requires continuous care. According to the 2018 Basic Health Research in Indonesia, the prevalence of DM was 1.5% nationally and 1.4% in South Kalimantan. The choice of drug type, potency and dosage form will vary depending on the clinical condition and severity of the patient. This study aims to determine the treatment profile of outpatient DM patients at the General Pharmacy Depot of Ulin Hospital Banjarmasin from January to March 2019. This study used an observational design. Data collection was carried out retrospectively. The data sources in this study were 65 prescriptions for DM patients who underwent outpatient treatment at the general depot of Ulin Hospital Banjarmasin from January - March 2019 with a total of 85 drug items. The sampling method used was total sampling method. Data collected included the drug name, class, potency, and dosage form. Research data were presented as percentages for each parameter. The results showed that the most prescribed antidiabetic drugs were Metformin 500 mg (48.2%), Glimepiride 2 mg (18.8%), Levemir Flexpen 100 IU/ml (11.7%), Novorapid Flexpen 100 IU. /ml (9.4%), Glimepiride 1 mg (4.7%), Gliquidone 30 mg (2.4%), Lantus Flexpen 100 IU/ml (1.2%), Metformin 850 mg (1.2%), Acarbose 50 mg (1.2%), and Acarbose 100 mg (1.2%). The most commonly prescribed diabetes drug classes are Biguanides (49.4%), Sulfonylureas (25.8%), Long-acting insulin (13.0%), short-acting insulin (9.4%), and Alpha Glucosidase Inhibitors (2.4%). Oral antidiabetic drug (77.6%) was more prescribed than injection dosage form (insulin) (22.4%).